2018
DOI: 10.5123/s1679-49742018000400003
|View full text |Cite
|
Sign up to set email alerts
|

Empresas de saneamento e a fluoretação da água dos sistemas de abastecimento: estudo ecológico nos municípios do Brasil, 2008/2010*

Abstract: Objective: to describe the characteristics of Brazilian sanitation utilities and municipalities according to the water supply system fluoridation situation. Methods: this was an ecological study using data from the National Survey of Basic Sanitation 2008, the Demographic Census 2010 and the Atlas of Human Development 2010. Results: of the 5,565 Brazilian municipalities, 60% had a fluoridation service; there was variation in fluoridation provision depending on the characteristics of the service providers and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
(23 reference statements)
1
4
0
3
Order By: Relevance
“…This study evaluated the effects of from regional characteristics, adjusted by factors associated with municipalities, on the lack of CWF provision. The associations between the outcomes and municipal characteristics reported in other studies were confirmed [ 3 - 5 ]. However, after the adjustment enabled by model 1, it was found that lower coverage of sewerage and wastewater collecting systems, lower human development, lower GDP per capita, and a higher percentage of expenditures spent on sanitation were strongly associated with a lack of CWF.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This study evaluated the effects of from regional characteristics, adjusted by factors associated with municipalities, on the lack of CWF provision. The associations between the outcomes and municipal characteristics reported in other studies were confirmed [ 3 - 5 ]. However, after the adjustment enabled by model 1, it was found that lower coverage of sewerage and wastewater collecting systems, lower human development, lower GDP per capita, and a higher percentage of expenditures spent on sanitation were strongly associated with a lack of CWF.…”
Section: Discussionsupporting
confidence: 80%
“…A study involving all Brazilian municipalities pointed out a possible relationship between the quality of sanitation services provided by companies and CWF. Municipalities with lower coverage of water and sewerage systems presented the lowest rates of CWF provision [ 5 ]. This information was refined in this research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Law No. 6.050, approved by the National Congress in 1974 in Brazil, made fluoridation mandatory everywhere a water treatment plant exists, creating conditions to universalize access to fluorides, studies have shown that the provision of water fluoridation is extremely unequal, both among macro-regions 14 and among municipalities in the country 15 . Nonetheless, the significance of the effect of specific variables linked to the concessionaire on the provision of public policy in the presence of characteristics linked to the municipalities, including the Brazilian macro-region to which it belongs, was not further investigated.…”
Section: Palavras-chavementioning
confidence: 99%
“…In the last decades, important advances have been made in the control of oral diseases in Brazil, mainly among schoolchildren 12,13 . These advances may be attributed to the fluoridation of the public water supply 14 , dissemination of fluoride toothpaste, decrease in sugar consumption 12 , as well as improvements in living conditions, and the implementation of public policies featured by expansion in health promotion actions 13 . However, dental caries and incidence of other oral diseases have increased due to the weakening of successful programs and policies 15 , with those most harmed being the most socially vulnerable 16 .…”
Section: Introductionmentioning
confidence: 99%